(untitled) (Encuentros, 2023)
A correlational scope study was carried out to identify the relationship between soft and social skills and the employability of graduates of a law program. A sample of 48 graduates was taken to whom the Soft Skills Scale and the Social Skills Check List were applied, and their employability was characterized. An analysis was carried out and the results only partially support the hypothesis of the relationship between social skills and employability, in particular with the relationship of job content; regarding soft skills, there are no differences associated with the employment situation, salary, hiring or relationship between work and career studied.